Poverty Alleviation of Women through Development of Cottage Industry in Cilegon Municipality, Banten - Muslikhin, Muslikhin (Bina Nusantara University, 2019)
This study aims to describe the implementation of the program of Cottage Industry (Industri Rumahan) in Cilegon Municipalty, Banten. Development of Cottage Industry (IR) is a program initiated by Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (KPPPA). The program will run for three years from 2016 to 2018. For 2016, the program is implemented in 14 districts and municipalities, one of which is Cilegon Municipality, Banten. Data collection is done by interviewing IR perpetrators and assistants. In addition, the data was collected by analyzing the documents such as the records of the implementing team meetings, the companion worker reports, mapping reports and mapping results analysis in the two urban villages that were the locations of IR development implementation. The validity test of data is done by triangulation of source and method.The study concluded that in general the implementation of IR development program in Cilegon Municipality, namely in Villages Ketileng and Bandengan, has followed the development pattern established by KPPPA. It's just that in some stages is not working properly. The stages that have problems are when determining the number of IR actors who get help and production equipment distribution. Many IR actors protest that they are not included in the IR development program. In addition to the production equipment that is distributed to IR actors, some are not in accordance with their needs so that less than the maximum.